A novel miRNA, Cse-miR-33, functions as an immune regulator by targeting CsTRAF6 in Chinese tongue sole (Cynoglossus semilaevis). Issue 134 (March 2023) - Li, Xihong; Chen, Yadong; Lin, Mengjiao; Wang, Jing; Wang, Na; Chen, Zhangfan; Chen, Songlin
Abstract: The tumor necrosis factor receptor-associated factor 6 (TRAF6) can act as a fundamental adaptor protein in a chain reaction of signal transduction and cascade events to finish off immune defenses. However, immunomodulatory research on TRAF6 gene is still limited in fish. In this study, a novel miRNA, Cse -miR-33 was identified from the whole genome of Chinese tongue sole ( Cynoglossus semilaevis ). After separate infections with three different Vibrio strains ( V. harveyi, V. anguillarum, V. parahemolyticus ) and one virus (nervous necrosis virus, NNV), the expressions of CsTRAF6 and Cse -miR-33 displayed significant time-dependent changes in immune related tissues and the trends were opposite in general. Through target gene prediction and dual luciferase reporter assay, Cse -miR-33 was proven to regulate CsTRAF6 by combining with 3′-UTR sequence of the gene. The results of qRT-PCR and western blotting (WB) analyses showed that Cse -miR-33 blocked the translation of CsTRAF6 protein at post-transcriptional level, rather than degrading the target mRNA. Further experiment indicated that Cse -miR-33 inhibitor largely reduced the death rate of Chinese tongue sole caused by V. harveyi and NNV. The expressions of CsTRAF 6-associated immune genes (such as CsIL-1R, CsMYD88, CsIRAK1, CsTNFα, CsIL6 and CsIL8 ) were also significantly changed in response to Cse- miR-33 agomir and inhibitor. The study suggested that Cse -miR-33 affected the immune response via targeting CsTRAF6 in C. semilaevis, which would provide us deep insights into miRNA-mediated regulatory network and help improve the immunity in fish. Highlights: Expressions of Cse -miR-33 and CsTRAF6 changed in response to Vibrio and virus. Cse -miR-33 blocked the translation of CsTRAF6 protein at post-transcriptional level. Cse -miR-33 affected V. harveyi - and NNV-caused death rate of Chinese tongue sole. Cse -miR-33 modulated CsTRAF6 -associated immune signaling pathways.